Estudio del Comportamiento Estructural de Bóvedas y Cúpula de la Estancia Jesuítica Santa Catalina, Provincia de Córdoba, Argentina - Gómez, J. L.; Ruata, M. E.; Nicasio, C.; Klein, K. (Revista ALCONPAT, 2014)
This job shows the study realized to test the dome structural behavior, of Jesuit SantaCatalina´s church and his vault, also novitiate´s vault and one room from the ranch, withdemonstrations of fissures.It describe a previously work at analysis tension, including a general 3D survey by a totalstation, in order to prepare the digital drawings and fundamentally determinate thethickness of the vaults and dome. Also realize two tangential wells to analyze thecharacteristics of the ground and the deepness of foundations. The sectional verificationwas made with Algor´s software analysis by very thin element from CAD solid models.The results of these studies allow assessing the safety vaults and dome structure, andpropose actions for the preservation and maintenance of this building declared culturalheritage of humanity by UNESCO.Keywords: dome, vaults, heritage, stress analysis